(416) Manpower Problems in Economic Development - Integrating Manpower Planning With General Planning مشكلات القوى العاملة في التنمية الاقتصادية - دمج تخطيط القوى العاملة مع التخطيط العام - Ogunsheya, Ayo (INP, 2024)
This study examines manpower planning as a fundamental component of economic development and emphasizes the necessity of integrating human resource planning into the broader framework of national economic planning. The paper argues that economic development depends not only on capital accumulation and natural resources but also on systematic planning of human resources to ensure the availability of skills and competencies required for sustainable development. The study begins by defining planning as a structured process for formulating policies and decisions intended to achieve predetermined objectives. Within the context of economic development, planning involves coordinating various elements including investment, production, consumption, employment, and human resource utilization. The author emphasizes that manpower planning should not be treated as an isolated activity but rather as an integrated element of comprehensive national development strategies. The research further discusses the distinction between labor supply and labor demand and explains that balancing economic requirements with educational and training outputs represents one of the most significant challenges facing developing economies. Special attention is given to the role of educational institutions and governmental bodies in forecasting future manpower requirements and designing policies capable of meeting those needs. The paper also addresses several employment-related issues, including open unemployment and disguised unemployment, particularly in agricultural sectors. Furthermore, it examines the policy dilemma concerning labor-intensive versus capital-intensive production techniques and their implications for employment and economic growth. Drawing upon experiences from India and other developing countries, the study argues that expanding employment opportunities should not occur at the expense of productivity and long-term economic efficiency. The academic contribution of this study lies in its development of an analytical framework linking education, training, employment policies, and development planning. The research therefore provides valuable insights for policy makers and researchers concerned with manpower development and economic planning in developing countries.